Optimizing Public Spaces for Age-Friendly Living: Renovation Strategies for 1980s Residential Communities in Hangzhou, China - Min Gong; Ning Wang; Yubei Chu; Yiyao Wu; Jiadi Huang; Jing Wu (Buildings)
Population aging and urbanization are two of the most significant social transformations of the 21st century. Against the backdrop of rapid aging in China, developing age-friendly community environments, particularly through the renovation of legacy residential communities, not only supports active and healthy aging but also promotes equity and sustainable development. This study focuses on residential communities built in the 1980s in Hangzhou, exploring strategies for the age-friendly renovation of outdoor public spaces. The residential communities that flourished during the construction boom of the 1980s are now confronting a dual challenge: aging populations and deteriorating facilities. However, existing renovation efforts often pay insufficient attention to the comprehensive age-friendly transformation of outdoor public spaces within these neighborhoods. Following a structured research framework encompassing investigation, evaluation, design, and discussion, this study first analyzes linear grid layouts and usage patterns of these communities. Then, the research team uses post-occupancy evaluation (POE) to assess the age-friendliness of outdoor public spaces. Semi-structured interviews with elderly residents identify key concerns and establish a preliminary evaluation framework, while a Likert-scale questionnaire quantifies the satisfaction with age-friendly features across four communities. The assessment reveals that key age-friendliness issues, including poor traffic safety, dispersed activity spaces, and insufficiently adapted facilities, are closely linked to the linear usage patterns within the spatial framework of the grid layouts. Based on the findings, the study develops tiered renovation goals, renovation principles and implemented an age-friendly design in the Hemu Community. The strengths, weaknesses, and feasibility of the renovation plan are discussed, while three recommendations are made to ensure successful implementation. The study is intended to provide a valuable reference for advancing age-friendly residential renewal efforts in Hangzhou and contributing to the broader objective of sustainable, inclusive city development.